FIRST RECORD OF PYRGUS CINARAE (LEPIDOPTERA: HESPERIIDAE) IN SERBIA (Acta Entomologica Serbica, 2014)
Pyrgus cinarae (Rambur, 1839) is currently known from eastern Spain, Albania, Macedonia, Greece, Bulgaria, Ukraine and Russia. At the end of June and beginning of July 2014 it was recorded in Serbia for the first time, expanding its known area of distribution in the Balkan Peninsula northwards. These records point out that southern Serbia may include several additional Mediterranean and Submediterranean species, and call for more systematic study and protection of butterflies in the region. The list of butterfly species recorded in Serbia has increased to a total of 199.